ANALYSIS OF RECURRENT BLEEDING IN THE SURGICAL TREATMENT OF COMPLICATIONS OF PEPTIC ULCER DISEASE AND PORTAL HYPERTENSION USING PEROXIDE HEMOSTASIS - Короткевич, Алексей Григорьевич; Савостьянов, Илья Васильевич; Леонтьев, Антон Сергеевич; Шестак, Инна Сергеевна; Май, Семен Александрович; Маринич, Яна Ярославовна (Medicine in Kuzbass, 2022)
The aim of the study was to analyze the causes and features of recurrence of upper gastrointestinal bleeding when using the technology of peroxide hemostasis in the surgical treatment of complications of peptic ulcer and portal hypertension. Methods and materials. Retrospective analysis of 410 medical records of patients admitted with signs of upper gastrointestinal bleeding to the general surgery department and subjected to endoscopic hemostasis in 2019-2021. Endoscopy was performed within an hour of admission. The main way to stop bleeding was submucosal infiltration of 1 % H2O2 solution 10-30 ml. The clinic of bleeding recurrence, endoscopic findings at recurrence and repeated endoscopy, the number of recurrences, the need for surgical hemostasis, treatment outcomes were taken into account. Results. The overall rebleeding rate was 7 %. There were four main sources of recurrent bleeding: chronic peptic ulcers of the stomach and duodenum bulb, esophageal varices and mucosal tears in Mellory-Weiss syndrome. Chronic peptic ulcers of the stomach and duodenum bulb were the most unfavorable in terms of recurrence rate. The recurrence rate of variceal bleeding was practically unchanged over the years of follow-up. Recurrences in 84 % of cases were noted in case of gastric ulcer diameter more than 1 cm. On the contrary, in case of duodenum bulb ulcers, half of recurrences occurred when the ulcer diameter was up to 1 cm. Vessel localization in the fundus was noted in all cases of recurrent bleeding. There was also an absolute predominance of men in recurrent bleeding. With recurrent bleeding after the second hemostasis and at the third rebleeding one out of 12 patients with peptic ulcer was operated on (8 %). Variceal bleeding recurred in 5 of 106 patients (5 %). Conclusion. Regular use of peroxide hemostasis in the treatment of upper gastrointestinal bleeding can significantly reduce the proportion of rebleeding, the need for surgical hemostasis, and overall mortality.